DISTRIBUSI LOGAM ESSENSIAL Cu DALAM SPONGE (PORIFERA) DI KEPULAUAN SPERMONDE - Lydia Melawaty; Alfian Noor; Tjodi Harlim; Nicole de Voogd (Marina Chimica Acta, 2012)
A research on essential metal distribution of copper in Spermonde waters has been carried out. Sponge species of Melophlus sarassinorum, Callyspongia aerizusa, dan Clathria reinwardtii were identified and analyzed accordingly. Copper level were measured using Inductrively Coupled Plasma Optical Emission Spectroscopy (ICP-OES) and the results showed that highest concentration was found in Clathria reinwartii  48.3 ppm. Copper distribution in sponge skeleton is higher than in its tissue and seemingly in terms of species the highest concentration is Clathria reinwartii taken from Barrang Lompo waters. In the meantime, Samalona waters contain highest concentration in its sedimen (3.96 ppm). Apparently Spermonde waters is beginning being interferred by metal pollution.